Safety Industry (Pencegahan K3 pada Industri Genteng) - Ginanjar Sasmito Adi; Siti Kholifah; Noer Afni Arifanti; Erika Novarinda (Indonesian Journal Publisher, 2023)
Occupational health and safety is a method used to protect workers from accidents and occupational diseases. This occupational safety and health effort does not only apply to the industrial sector such as manufacturing, mining, construction, this also applies to the small industrial sector such as the tile-making industry. The purpose of this community service is to provide health education to tile industry workers related to health and work safety. This service activity was carried out at UD Genteng Baru Muncul Jember. The results of the community service carried out in the tile industry showed an increase in knowledge from the average pre-test was 12.7 and the post-test was 14 (the highest score was 15). Another result of this service shows that health complaints among tile industry workers are pain in the joints and back and fatigue due to heat and thirst, several other complaints that arise include cough, shortness of breath, visual and hearing impairment. Work accidents that have occurred to workers include machine injuries and falls. Occupational health and safety must be a concern for business owners with regard to providing a safe environment as well as appropriate personal protection and balanced by obedient behavior of workers in using the prescribed personal protection.